PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. ZULU ALPHA PAPA JAKARTA SELATAN - Angga Pratama; Yulies Herni; Dira Karlina (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The purpose of this research is to determine the influence of the work environment and organizational culture on employee performance at PT. Zulu Alpha Papa in South Jakarta, both partially and simultaneously. The method used is quantitative. Data analysis includes validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing.The results of this research show that the work environment has a significant influence on employee performance with the regression equation Y = 13.740 + 0.648X1, and a correlation value of 0.714, indicating a strong relationship between the two variables. The coefficient of determination is 0.510. The hypothesis testing shows that the calculated t-value is greater than the tabled t-value (9.186 > 1.990).Furthermore, organizational culture also has a significant influence on employee performance with the regression equation Y = 16.082 + 0.598X2 and a correlation value of 0.665, indicating a strong relationship between the two variables. The coefficient of determination is 38.2%. The hypothesis testing shows that the calculated t-value is greater than the tabled t-value (7.082 > 1.990).Both the work environment and organizational culture simultaneously have a significant influence on employee performance with the regression equation Y = 8.775 + 0.487X1 + 0.298X2. The correlation value is 0.757, indicating a strong relationship between the independent variables and the dependent variable. The coefficient of determination is 57.3%, while the remaining 42.7% is influenced by other factors. The hypothesis testing shows that the calculated F-value is greater than the tabled F-value (53.748 > 2.720).